Identificación morfo-agronómica y rendimiento en cultivares de arroz (Oryza sativa L.) en el cantón Babahoyo - provincia de Los Ríos. - Bustamante Lucio, Adonis Rafael (2025)
The main purpose of this research was to evaluate the performance of various rice cultivars in the Babahoyo canton, Los Ríos province, in order to select those with the best production and good agronomic characteristics. The experimental design applied in this study was analysis of variance (ANOVA), and the Tukey test was used to compare the means of the evaluated variables (p < 0.05). Euclidean analysis was also used to group cultivars based on genetic similarity. Finally, a frequency analysis was performed, where 81 cultivars were grouped into classes to select the best cultivars, primarily considering yield characteristics (g/plant), number of panicles per plant, and hulled grain length (mm). In all three cases, the "bigger is better" designation was used.The sample consisted of 81 cultivars, each with varying numbers of individuals. The following variables were evaluated: days to flowering, vegetative vigor, plant height (cm), number of tillers per plant, number of panicles per plant, panicle length (cm), total number of grains per panicle, percentage of empty grains per panicle, length (mm) and width (mm) of hulled and unhulled grains; and yield (g/plant).A total of 21 individuals were selected for their best yield from 17 rice cultivars, which presented values between 117.4 and 216.5 g/plant. Twenty-seven individuals with the highest number of panicles were identified from 22 rice cultivars. These 27 selected individuals presented values between 42 and 96 panicles per plant. Thirty-four individuals with the best average hulled grain length from 22 cultivars were selected, presenting values between 7.33 and 8.1 mm.